Are women more credit constrained? : experimental evidence on gender and microenterprise returns - De Mel, Suresh, 1964- 1964- (Policy research working paper, 2008)
"This paper analyzes data from a randomized experiment on mean returns to capital in Sri Lankan micro-enterprises. The findings show greater returns among men than among women; indeed, returns were not different from zero for women. The authors explore different explanations for the lower returns among female owners, and find no evidence that the gender gap is explained by differences in ability, risk aversion, or entrepreneurial attitudes. Differential access to unpaid family labor and social constraints limiting sales to local areas are not important. However, there is evidence that women invested grants differently from men. A smaller share of the smaller grants remained in the female-owned enterprises, and men were more likely to spend the grant on working capital and women on equipment. The gender gap is largest when male-dominated sectors are compared with female-dominated sectors, although female returns are lower than male returns even for females working in the same industries as men. The authors examine the heterogeneity of returns to determine whether any group of businesses owned by women benefit from easing capital constraints. The results suggest there is a large group of high-return male owners and a smaller group of poor, high-ability, female owners who might benefit from more access to capital. "--World Bank web site